2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Participation in VEX Robotics Competition on Middle and High School Students’ Interest in Pursuing STEM Studies and STEM-related Careers

Abstract: Alemdar has experience evaluating programs that fall under the umbrella of educational evaluation, including K-12 educational curricula, after-school programs, and comprehensive school reform initiatives. Across these evaluations, she has used a variety of evaluation methods, ranging from multi-level evaluation plan designed to assess program impact to methods such as program monitoring designed to facilitate program improvement. Her leadership evaluation work includes serving as a lead evaluator on NASA's ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Jackson et al (2019) found that the interest gains following participation in the robotics lessons were the same for both gender and lesson type. However, some mixed or anecdotal evidence has showed the success of robotics programs in influencing girls' engineering perceptions (Hendricks et al, 2012). Moreover, some other findings observations regarding robotics and gender noted that educational robots might contribute to decreasing gender gaps in STEM fields (Diekman et al, 2011;Terry et al, 2011).…”
Section: Moderator Variablesmentioning
confidence: 99%
“…Jackson et al (2019) found that the interest gains following participation in the robotics lessons were the same for both gender and lesson type. However, some mixed or anecdotal evidence has showed the success of robotics programs in influencing girls' engineering perceptions (Hendricks et al, 2012). Moreover, some other findings observations regarding robotics and gender noted that educational robots might contribute to decreasing gender gaps in STEM fields (Diekman et al, 2011;Terry et al, 2011).…”
Section: Moderator Variablesmentioning
confidence: 99%
“…Students are taught how to build and program robotic devices in engaging and hands-on ways and promote learning in a playful environment (Johnson, 2003;Malec, 2001;Yuan et al, 2019). The findings on the impact of robotics/robotic devices in education show that it generates a significant level of students' interest and desire to pursue STEM careers (Chen & Chang, 2018;Hendricks et al, 2012;Nugent et al, 2010). Afari and Khine (2017), in their study exploring the educational use of robotics in schools, concluded that the use of robotics improved students' problem-solving and computational skills.…”
Section: Robotics-based Educationmentioning
confidence: 99%
“…One way of fostering the development of these CT concepts has been to implement classroom‐based activities using educational robotics, especially in K‐12 STEM education (Chevalier et al, 2020). Since the collaboration between LEGO Group and the Massachusetts Institute of Technology (MIT) Media Lab to develop educational robotics, education research has exploded in the number of studies investigating the academic impact of ERs (Alimisis, 2013; Eguchi, 2014; Hendricks et al, 2012; Witherspoon et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%